Cold Ceramic in Endodontics Treatments: A Review - Amin Roshani; Seyyed Amirali Hashemi Baraz; Iman Shiezadeh (Journal of Craniomaxillofacial Research)
Introduction: Cold Ceramic (CC) is designed to meet the ideal criteria for root filling materials, offering effective sealing, biocompatibility, non-toxicity, dimensional stability, insolubility in tissue fluids, radiopacity, and ease of handling. It sets in the presence of moisture, making it suitable for various endodontic applications such as root-end filling, root perforation repair, apical barriers in teeth with open apices, and pulp capping. This study aims to evaluate cold ceramic’s clinical outcomes and applications as presented in case reports. Materials and Methods: A comprehensive literature search was conducted to identify published case reports and case series on the clinical application of cold ceramics in endodontics from January 2000 to April 2024.  Databases searched included PubMed, MEDLINE, Scopus, Web of Science, Cochrane Library and Google Scholar. The search terms used were “cold ceramic,” “bio ceramic,” “endodontics,” “case report,” “clinical outcomes,” and “dental materials”. Articles in English and Persian were included. Patient demographics, cold ceramic brand, clinical procedures, outcomes, follow-up periods, and any complications were extracted. Quality assessment of the included case reports was performed using the CARE guidelines. Results: After removing duplicates and screening titles and abstracts, 7 case reports and 2 case series met the inclusion criteria. The reviewed case reports included 16 patients (9 female and 7 male) with a mean age of 29.25±1.2. Clinical outcomes were generally favorable, with high success rates and minimal complications reported. Conclusion: All cases demonstrated radiographic and clinical healing and an absence of postoperative pain or infection during follow-up periods ranging from 3 months to 4 years. cold ceramics provide promising success rates and negligible complications in various clinical endodontic scenarios. Keywords: Apexification; Biocompatibility; Case report; Cold ceramic; Endodontics; Root canal; Root perforation; Sealing ability; Treatment.